Product Improvement Strategy for Micro, Small, and Medium Enterprises through Halal Certification Program in Metro City - Yusniarti, Astri (Journal of Contemporary Applied Islamic Philanthropy, 2024)
Purpose: The purpose of this study is to find out the efforts made by MSME players in the city of Metro to obtain halal certificates as their business legality. Methodology: This research is field research that directly obtains data from primary data sources through interviews and is supported by documentation of information related to this research.  Findings: Most of the MSMEs in metro cities get halal certificates from the Free Halal Certification (Sehati) program whose process is guided and assisted by certified Halal Product Assistance Officers (P3H). This halal certificate is one of the efforts of MSMEs to improve their products so that they can compete in local and international markets. MSME players should maintain the halal standards of their products after obtaining halal certificates so that these products remain of high quality and have competitiveness with local and international products. The Metro City Government through related agencies plays an important role in improving MSME products by ensuring the quality, and halalness of products so that they have competitiveness with products outside the region and also international products. The strategy developed by the Metro City Government was enthusiastically welcomed by MSME players in Metro City. This strategy can improve the economy of MSME players and also plays a role in improving the economy of Metro City.